First record of the Early Toarcian Oceanic Anoxic Event from the Southern Hemisphere, Neuquén Basin, Argentina - Al Suwaidi, Aisha (2010)
The first record of the Early Toarcian Oceanic Anoxic Event (c. 183 Ma) from the Southern Hemisphere is described from the Neuque´n Basin, Argentina, identified chemostratigraphically on the basis of a relative increase in marine organic carbon and a characteristic negative carbon-isotope excursion ( 13Corg) in bulk rock and fossil wood. The negative excursion of 26‰ in bulk organic carbon (falling to 231.3‰) crosses the boundary of the tenuicostatum–hoelderi Andean ammonite Zones, equivalent to the tenuicostatum–falciferum/serpentinum zones of Europe. These data indicate that the Early Toarcian Oceanic Anoxic Event was a global phenomenon.